MOTHER’S KNOWLEDGE, PARENTING STYLE, AND MOTOR DEVELOPMENT IN STUNTING AND NON-STUNTING TODDLER - Syandri, Fadriaz; Latifah, Melly (Journal of Child, Family, and Consumer Studies, 2024)
The stunting rate in Indonesia is still above the maximum figure set by WHO. Stunting impacts a child's physical growth and various child developments, one of which is motor development. In general, this research aims to analyze the influence of mother knowledge and parenting style on the development of gross motor and fine motor skills in toddlers. This research used an explanatory design involving 80 examples of families with stunted and non-stunted toddlers aged 2-3 years in Sindang Barang and Bubulak Villages selected by purposive sampling. Stunted toddlers are more commonly found in boys, low maternal education, low family income, large family members, and low maternal knowledge. The correlation test results show a significant positive relationship between children's stunting status and their mother's knowledge. The father's and mother's education is related to the mother's knowledge, and the father's education and family income are associated with the authoritative parenting style. The results of the influence test show that the authoritarian parenting style significantly positively influences children's gross motor and fine motor development.